Poškodbe otrok pri športni dejavnosti v zadnjem triletju osnovne šole - Gregorčič, Matjaž (Šport (Ljubljana), 2019)
Purpose of this study was to analyze injuries of children due to sports activities undertaken in the last three years of elementary school. The study analyzed the injuries that occured during Physical Education, participation in sport clubs and leisure activites. The data was collected using a questionnaire on a sample of 631 pupils, 282 boys (44,7%) and 349 girls (53,9%), attending the last three years of elementary school; eight Slovenian elementary schools in the Goriška, Gorenjska and Osrednjeslovenska regions were chosen for the research. The results of the study showed that 32,2% of students suffered an injury during PE in school year 2016/17. The obtained data do not show statistically significant differences in the number of injuries suffered in PE classes in relation to gender or age. The findings show that the greatest number of injuries suffered during PE classes were mostly wounds, followed by muscle injuries and sprains; the knee, ankle in fingers were parts of the body that were injured the most frequently. We found statistically significant differences in the number of injuries sustained in PE classes and those experienced in a sports club. Students suffered more injuries during sports activities in sport clubs than PE. There were significantly less injuries during leisure activities than sport activities in PE. Differences in the time of absence after injury experienced in PE classes and club/society attendance can be spotted. Students were absent more time after injuries in sport clubs than injuries in PE. while there are no statistically significant differences in absence regarding sports activities in PE and a free-time leasure activity. The highest number of injuries sustained in school was recorded in ball games; for boys in football, and for girls in volleyball. In the activities of the sports club or the society, the culprit for the highest number of injuries in boys were martial arts, and in girls, dance. In their spare time, boys suffered the most injuries during football and cycling, while girls experienced injuries due to running, rollerblading and roller skating.
Keywords: children; elementary school; injury; leisure time; osnovne šole; otroci; physical education; poškodbe; prosti čas; sport; sports activity; šport; športna dejavnost; športna vzgoja